Control, data acquisition and analysis of catalytic gas—liquid mini slurry reactors using a personal computer - Mohammadi, N.A.; Rempel, G.L. (Computers & chemical engineering, 1987)
An automated gas-consumption measuring system is designed which can be used to keep constant or time-variable pressure and record continuously the consumption or production of gases in a batch-type microreactor. Process control, data acquisition and analysis is carried out using a personal computer (IBM) and a Lab-master (Tecmar Inc.) interface device. Hardware and software was designed and developed for the system. A direct digital feedback control loop is employed to keep constant or time-variable pressure in the batch-type slurry reactor. In order to investigate the dynamic behavior of the system, mathematical analysis for a continuous and a sampled system is presented. The application of the system is illustrated for a kinetic run involving the catalytic hydrogenation of an acrylonitrile-butadiene copolymer in the liquid phase. Scope—There are numerous types of chemical reactions which involve gas consumption or production. Batch-type reactors are commonly employed in kinetic studies of such reactions. Presently, manual techniques are used where the operator adjusts the pressure in the reactor at specific time intervals and measures the gas supplied. Alternatively, sampling techniques are used where samples are withdrawn from the gaseous or liquid phase and subsequently analyzed. The major disadvantages with these manual techniques however are the relatively large sampling period and/or difficulty in data collection which makes the study tedious and often subject to considerable error. The computer-controlled system presented in this paper, besides providing for facile reaction control, enables the aquisition of reliable kinetic data and its immediate analysis with a high degree of precision. Conclusions and Significance—Hardware, software and system analysis of a newly-designed computer-controlled batch-type reactor has been developed. From the excellent reproducibility obtained with the system for the hydrogenation of several substrates, it can be concluded that the system can be successfully and conveniently employed for kinetic studies of a variety of gas-producing/gas-consuming reactions, with constant or operator-specified variable pressure. Results of a system analysis, carried out in this investigation, indicate that the system is inherently stable when an analog controller is used, as shown by equation (19) (reactor pressure response for a step input in the reaction rate). However, the stability of the system depends on sampling period when a digital controller is employed, as shown by equation (20) (reactor pressure response for a step input in the reaction rate).